Outside the fold : conversion, modernity, and belief - Viswanathan, Gauri (New Jersey : Princeton university press, 1998)
"Outside the Fold is a radical reexamination of religious conversion. Gauri Viswanathan skillfully argues that conversion is an interpretive act that belongs in the realm of cultural criticism. To that end, this work examines key moments in colonial and postcolonial history to show how conversion questions the limitations of secular ideologies, particularly the discourse of rights central to both the British empire and the British nation-state. Implicit in such questioning is an attempt to construct an alternative epistemological and ethical foundation of national community. Viswanathan grounds her study in an examination of two stimultaneous and, she asserts, linked events: the legal emancipation of religious minorities in England and the acculturation of colonial subjects to British rule. The author views these two apparently disparate events as part of a common pattern of national consolidation that produced the English state. She seeks to explain why resistance, in both cases, frequently took the form of religious conversion, especially to "minority" or alternative religions. Confronting the general characterization of conversion as assimilative and annihilating of identity, Viswanathan demonstrates that a willful change of religion can be seen instead as an act of opposition. Outside the Fold concludes that, as a form of cultural crossing, conversion comes to represent a vital release into difference."
"Through the figure of the convert, Viswanathan addresses the vexing question of the role of belief and minority discourse in modern society. She establishes new points of contact between the convert as religious dissenter and as colonial subject. This convergence provides a transcultural perspective not otherwise visible in literary and historical texts. It allows for radically new readings of significant figures as diverse as John Henry Newman, Pandita Ramabai, Annie Besant, and B.R. Ambedkar, as well as close studies of court cases, census reports, and popular English fiction. These varying texts illuminate the means by which discourses of religious identity are produced, contained, or opposed by the languages of law, reason, and classificatory knowledge. Outside the Fold is a challenging, provocative contribution to the multidisciplinary field of cultural studies. Book jacket."--Jacket
pt. 1. Dissent and the Nation. Ch. 1. Cross Currents. Ch. 2. A Grammar of Dissent pt. 2. Colonial Interventions. Ch. 3. Rights of Passage: Converts' Testimonies. Ch. 4. Silencing Heresy. Ch. 5. Ethnographic Plots. Ch. 6. Conversion, Theosophy, and Race Theory pt. 3. The Imagined Community. Ch. 7. Conversion to Equality. Ch. 8. Epilogue: The Right to Belief. Appendix. The Census of India, 1901
Includes bibliographical references (pages [297]-315) and index
Keywords: Conversion -- Comparative studies; Religion and culture -- Comparative studies; Religion and politics -- Comparative studies; India -- Religion -- 19th century; India -- Religion -- 20th century; Conversion -- Comparative studies; India -- Religion -- 19th century; India -- Religion -- 20th century; Religion and culture -- Comparative studies; Religion and politics -- Comparative studies